Evaluation of Anxiolytic Activity of Stellaria media Linn. Extracts in Mice - Arora, Disha; Sharma, Anupam (Pharmacognosy Communications)
Background: Stellaria media Linn. (Caryophyllaceae) has been traditionally used for a variety of ailments such as inflammation, blood diseases, eczema and nerve diseases. The present study was designed to evaluate the anxiolytic activity of various extracts of S. media in mice using the widely used elevated plus-maze (EPM) model. Materials and Methods: Test mice were administered a variety of extracts viz. petroleum ether, chloroform, methanol and water at four different dose levels (50, 100, 200 or 400 mg/kg, po), and compared with the standard anxiolytic drug, diazepam (2 mg/kg, po). Anxiolytic activity was confirmed by using an actophotometer. The methanol extract was also subjected to phytochemical screening. Results: The methanol extract (100 mg/kg) exhibited significant anxiolytic activity as evidenced by an increase in both the time spent in the open arms and the number of open arm entries. This effect was comparable to that produced by diazepam. Significant increase in the locomotory behavior of mice by the methanol extract, further confirmed its anxiolytic activity. Phytochemical screening of the methanol extract showed the presence of flavonoids, triterpenoids, proteins, tannins, carbohydrates, fixed oils and fats. Conclusion: The results indicate that the anxiolytic activity of S. media resides in its methanol extract.
Keywords: anxiolytic; elevated plus-maze; locomotor activity; Stellaria media